Public-private partnership in achievement of competitiveness - Trivun, Veljko (Array, 2008)
Summary: 'Public services' is a term mostly used to refer to services provided by government to its citizens, either directly through public sector or by financing private provision of services or by ceding these services to the private sector. Privatization of the public sector is an inevitability that will sooner or later enter the agenda of various state structures in Bosnia and Herzegovina as well. State sector will not be able to survive the market race with the private sector, and will have to entrust part of its functions to the private sector fully, partly, or through a combination of PPP models. In most cases, public services are provided by specialized organisations (e.g. education, provided by public institutions but increasingly by privately-owned ones as well), or public enterprises now in the already obligatory form of company, either corporation or limited liability company.